Implementasi Pembelajaran Materi Thaharah di SMP Muhammadiyah 2 Blitar - Abdul Rozak Ali Maftuhin; Romelah Romelah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The learning process serves as a pathway to achieving basic competencies within curriculum implementation. This study aims to describe the implementation of teaching and its evaluation on the topic of thaharah, specifically in the chapter on wudu. The research approach employed is qualitative, with a case study methodology. The researcher collected data through interviews with teachers and students, documentation, and observation during the learning process. The findings indicate that the teaching implementation was carried out optimally, including opening activities such as greetings and providing motivation, core activities such as explaining and demonstrating lessons, and closing activities such as reflection and question-and-answer sessions. The assessment conducted by the teacher aligns with the demands of the Kurikulum Merdeka, which requires evaluation from cognitive, psychomotor, and affective aspects as part of an authentic assessment approach.